A deep learning approach towards soft biometrics attributes prediction using CNN - Kibria, Maharab; Tabassum, Ilmi; Ahmed, Fardin; Habib, Nahian (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.